Comparative analysis of selected Personal Bibliographic Management Software (PBMS) with special reference to the requirements of researchers at a University of Technology - Omar, Yunus (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Information Science))--University of Stellenbosch, 2005.